Advances in the Development of Single‐Atom Catalysts for High‐Energy‐Density Lithium–Sulfur Batteries. Issue 30 (7th June 2022) - Liang, Ziwei; Shen, Jiadong; Xu, Xijun; Li, Fangkun; Liu, Jun; Yuan, Bin; Yu, Yan; Zhu, Min
Abstract: Although lithium–sulfur (Li–S) batteries are promising next‐generation energy‐storage systems, their practical applications are limited by the growth of Li dendrites and lithium polysulfide shuttling. These problems can be mitigated through the use of single‐atom catalysts (SACs), which exhibit the advantages of maximal atom utilization efficiency (≈100%) and unique catalytic properties, thus effectively enhancing the performance of electrode materials in energy‐storage devices. This review systematically summarizes the recent progress in SACs intended for use in Li‐metal anodes, S cathodes, and separators, briefly introducing the operating principles of Li–S batteries, the action mechanisms of the corresponding SACs, and the fundamentals of SACs activity, and then comprehensively describes the main strategies for SACs synthesis. Subsequently, the applications of SACs and the principles of SACs operation in reinforced Li–S batteries as well as other metal–S batteries are individually illustrated, and the major challenges of SACs usage in Li–S batteries as well as future development directions are presented. Abstract : The cycling stability and rate performance of Li–S batteries are adversely affected by the formation of Li dendrites and the polysulfide shuttle effect. Single‐atom catalysts (SACs) can effectively guide Li deposition and suppress polysulfide migration, thus holding great promise for Li–S batteries. The recent progress in the development of SACs for Li–S batteries is systematically summarized and analyzed.